Concurrent Use of Oral Anticoagulants and Sulfonylureas in Individuals With Type 2 Diabetes and Risk of Hypoglycemia: A UK Population-Based Cohort Study - Alwafi, Hassan; Wong, Ian C. K.; Naser, Abdallah Y.; Banerjee, Amitava; Mongkhon, Pajaree; Whittlesea, Cate; Alsharif, Alaa; Wei, Li (Frontiers in Medicine, 2022)
Objective To investigate the association of concurrent use of oral anticoagulants (OACs) and sulfonylureas and the risk of hypoglycemia in individuals with type 2 diabetes mellitus (T2DM). Research Design and Methods A retrospective cohort study was conducted between 2001 and 2017 using electronic primary healthcare data from the IQVIA Medical Research Data (IMRD) that incorporates data supplied by The Health Improvement Network (THIN), a propriety database of Cegedim SA. Individuals with T2DM who received OAC prescription and sulfonylureas were included. We compared the risk of hypoglycemia with sulfonylureas and OACs using propensity score matching and Cox regression. Results 109,040 individuals using warfarin and sulfonylureas and 77,296 using direct oral anticoagulants (DOACs) and sulfonylureas were identified and included. There were 285 hypoglycemia events in the warfarin with sulfonylureas group (incidence rate = 17.8 per 1,000 person-years), while in the sulfonylureas only, 304 hypoglycemia events were observed (incidence rate = 14.4 per 1,000 person-years). There were 14 hypoglycemic events in the DOACs with sulfonylureas group (incidence rates = 14.8 per 1,000 person-years), while in the sulfonylureas alone group, 60 hypoglycemia events were observed (incidence rate =23.7 per 1,000 person-years). Concurrent use of warfarin and sulfonylureas was associated with increased risk of hypoglycemia compared with sulfonylureas alone (HR 1.38; 95% CI 1.10–1.75). However, we found no evidence of an association between concurrent use of DOACs and sulfonylureas and risk of hypoglycemia (HR 0.54; 95% CI, 0.27–1.10) when compared with sulfonylureas only. Conclusions We provide real-world evidence of possible drug-drug interactions between warfarin and sulfonylureas. The decision to prescribe warfarin with coexistent sulfonylureas to individuals with T2DM should be carefully evaluated in the context of other risk factors of hypoglycemia, and availability of alternative medications.